1982
DOI: 10.1021/bi00266a029
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization using circular dichroism and fluorescence spectroscopy of a stable intermediate conformation formed in the denaturation of bovine carbonic anhydrase with guanidinium chloride

Abstract: Particularly stable elements of noncovalent structure in bovine carbonic anhydrase have been detected and studied. These are present in a highly populated intermediate state formed during denaturation of the enzyme with guanidinium chloride. The intermediate has been detected by analysis of the denaturation profiles, and some of its structural properties have been characterized by CD and fluorescence spectroscopy, including fluorescence polarization and lifetime measurements. Measurements have been made on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 31 publications
(42 reference statements)
6
53
0
Order By: Relevance
“…676,685 Henkens et al found that the fluorescence depolarization for BCA was low in both the native and molten-globule states, a result that suggests that the Trp residues were relatively immobilized in both states. 678 Furthermore, the emission wavelength of the molten-globule state was red-shifted (by 3 nm) as compared to the native state; this result reveals that Trp residues in the molten-globule state experience a less hydrophobic environment than in the native protein. Taken together, these results suggest that the environment surrounding Trp in the molten globule is compact (similar to the native state), but that the tertiary structure of the native state has not yet formed.…”
Section: Lack Of Tertiary Structurementioning
confidence: 90%
See 2 more Smart Citations
“…676,685 Henkens et al found that the fluorescence depolarization for BCA was low in both the native and molten-globule states, a result that suggests that the Trp residues were relatively immobilized in both states. 678 Furthermore, the emission wavelength of the molten-globule state was red-shifted (by 3 nm) as compared to the native state; this result reveals that Trp residues in the molten-globule state experience a less hydrophobic environment than in the native protein. Taken together, these results suggest that the environment surrounding Trp in the molten globule is compact (similar to the native state), but that the tertiary structure of the native state has not yet formed.…”
Section: Lack Of Tertiary Structurementioning
confidence: 90%
“…685 In addition to promoting folding to an intermediate state, the metal cofactor facilitates folding to the native enzyme. 678,704 Cobalt can replace Zn II in the active site of CA without major structural changes or significant loss of activity (see section 5). Co II can be observed directly by absorption (at 550 nm) or indirectly by fluorescence (it quenches the fluorescence of Trp residues of CA) 702 and, thus, can convey information on conformational changes occurring near the binding site of the metal ion during refolding (see section 8.3).…”
Section: Metal Cofactormentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, when the native active site is altered, DNSA looses its affinity. When DNSA dissociates from the active site the emission spectrum becomes red shifted and the intensity drops [28]. For HCAIIp W t only a small drop in the fluorescence intensity and a minor change in the wavelength of maximum intensity were observed (Fig.…”
Section: Probing the Active Site By Dnsa Bindingmentioning
confidence: 92%
“…Carlsson et al [16,17] suggested that an 'incorrectly folded' form of HCAB might accumulate at medium concentrations of GuCl. Henkens et al [24] characterized an intermediate form of the bovine enzyme at 2 M GuCI; McCoy and Wong [20] have shown that the kinetics of renaturation of the same enzyme is consistent with the presence of intermediate forms; and Ptitsyn's group has suggested that bovine carbonic anhydrase has a molten globular form in 2 M GuCl, similar to those obtained in a few other globular proteins [8]. Such a molten globule is defined as possessing a secondary structure comparable to the native form, but lacking tertiary structural features, or cooperative thermal melting.…”
Section: Time In Minmentioning
confidence: 99%